Digital Teaching Materials for Explanatory Texts in Improving Literacy of SMP/MTs Students - Yuliarto; Jaja; Khaerudin, I. Robia (International Journal of Educational Research Excellence (IJERE), 2025)
The Korean Wave has spread increasingly across various countries, with social media and peer groups serving as its primary channels of dissemination. Traditional values play an important role in adolescents’ decisions to adopt cultural elements from the Korean Wave phenomenon. This study aimed to analyze the influence of social media access, traditional values, and peer interaction on adolescents’ Korean Wave behavior. A quantitative research design was used, involving 100 adolescent Korean fans purposively selected from the Greater Jakarta area (Jabodetabek). Data were collected online using Google Forms and analyzed using SPSS and SmartPLS. The SEM analysis results show that the Korean Wave behavior is influenced by social media access, traditional values, and peer interaction. Social media access and peer interaction were found to have a direct positive effect on Korean Wave behavior. Additionally, social media access had an indirect effect on Korean Wave behavior through peer interaction. In contrast, traditional values were found to have a significant negative effect on Korean Wave behavior. It is recommended that the government adopt creative strategies to rebrand local culture to remain competitive in the era of cultural globalization amid the Korean Wave phenomenon. Raising adolescents’ awareness and appreciation of Indonesian culture is also essential and can be fostered through school activities and the internalization of cultural values within families